(untitled) (Med Phoenix, 2017)
Background: This study reports the comparative studies and microbial risk assessment of different water samples used for drinking water. The results obtained were compared with WHO and EPA standards for drinking and recreational water. Methods: Physicochemical and bacteriological analysis of water samples were carried out from source, taps, well and stone spouts used for drinking purpose in Tokha (Saraswati and Chandeswari Village Development Committee). Total viable count was carried out by pour plate technique. Total coli form and fecal coli form were performed by membrane filtration technique. The results obtained were compared with World Health Organization (WHO), National Agency for Food and Drug Administration and Control (NAFDAC) and Nepal Standard of Drinking Water Quality (NSDWQ) standards for drinking water. Results: The pH, total hardness, chloride, nitrate and arsenic content of samples were found within permissible guideline value however well sample was found to exceed Nepal standard values for calcium hardness and ammonia content. The total viable counts for all the water samples were high exceeding the limit for water (1.0×102 cfu/ ml). All the water samples were found to contain coli forms and fecal organisms in numbers greater than the required WHO/FAO standards for water. The fecal coli form colonies on M-endo agar plate ranged between 143 and 152 and total coli form from 110 to 248 per 100 ml water also exceed the standard limit for water. The Isolated organisms were identified to be E.coli, Klebsiella spp. And Citrobacter spp. MED Phoenix Volume (1), Issue (1) July 2016, page: 15-18